2020
DOI: 10.3847/2041-8213/ab6bd9
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Diatomic Carbon in 2I/Borisov

Abstract: 2I/Borisov is the first-ever observed interstellar comet (and the second detected interstellar object). It was discovered on 30 August 2019 and has a heliocentric orbital eccentricity of ∼ 3.35, corresponding to a hyperbolic orbit that is unbound to the Sun. Given that it is an interstellar object, it is of interest to compare its properties -such as composition and activity -with the comets in our Solar System. This study reports low-resolution optical spectra of 2I/Borisov. The spectra were obtained by the M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 30 publications
6
17
1
Order By: Relevance
“…However, the spectrum could also be consistent with a non-organic, iron-rich surface ('Oumuamua ISSI Team, 2019). While some observations of C2 and CN in 2I/Borisov suggest it is comparable to some of the most carbon-depleted comets in our solar system (Fitzsimmons et al, 2019;Opitom et al, 2019;Lin et al, 2020), more recent reports that examine the time history 2I/Borisov's cometary activity suggest it may only be barely depleted (Bannister et al, 2020). Thus, the presence or absence of organic compounds in either object is uncertain.…”
Section: Science Objectivementioning
confidence: 66%
“…However, the spectrum could also be consistent with a non-organic, iron-rich surface ('Oumuamua ISSI Team, 2019). While some observations of C2 and CN in 2I/Borisov suggest it is comparable to some of the most carbon-depleted comets in our solar system (Fitzsimmons et al, 2019;Opitom et al, 2019;Lin et al, 2020), more recent reports that examine the time history 2I/Borisov's cometary activity suggest it may only be barely depleted (Bannister et al, 2020). Thus, the presence or absence of organic compounds in either object is uncertain.…”
Section: Science Objectivementioning
confidence: 66%
“…Early observations, mainly with optical low-resolution spectrographs, showed that 2I is depleted in C 2 , similarly to So-E-mail: copi@roe.ac.uk lar System carbon-chain depleted comets (Fitzsimmons et al (2019); Opitom et al (2019a); Bannister et al (2020); Kareta et al (2020); Lin et al (2020); Aravind et al (2021)). Later, Cordiner et al (2020) and Bodewits et al (2020) reported that 2I is very rich in CO relative to both water and HCN, more than any Solar System comet observed within 2.5 au from the Sun.…”
Section: Introductionmentioning
confidence: 78%
“…Later, de León et al (2020), Opitom et al (2019) and Kareta et al (2020), have all reported the clear detection of CN along with an upper limit to the production rate of C 2 (0-0) emissions. Lin et al (2020) and Bannister et al (2020) have reported the clear detection of both CN and C 2 in their spectrum, with the latter work having the most detailed spectrum of 2I/Borisov reporting the detection of well-resolved C 2 , NH 2 and CN emissions. In this paper, we discuss the spectroscopic and imaging observations carried out from two Indian observatories during November and December 2019, to study the evolution of molecular emissions and also to put constraints on the physical characteristics of the rare interstellar comet 2I/Borisov.…”
Section: Introductionmentioning
confidence: 94%